Rationale and design for the thoracic Paravertebral Adjunctive Dexamethasone Palmitate Reducing chronic pain After cardiac surgery (PANDORA) trial: a parallel-group, double-blinded, randomised controlled, single-centre study - Jing Zhao; Hui Zhang; Ziyu Zheng; Baobao Gao; Lini Wang; Chong Lei; Hailong Dong; Taoyuan Zhang; Jiao Gao; Lihong Hou (BMJ Open)
Introduction Minimally invasive cardiac surgery (MICS) is important for enhanced recovery in cardiac surgery. However, the incidence of chronic postsurgical pain (CPSP) is high and is associated with worsened quality of recovery and life, as well as raised short-term or long-term mortality. The mechanism is not clear, and there is still a lack of safe and effective preventive measures.Methods and analysis The Paravertebral Adjunctive Dexamethasone Palmitate Reducing chronic pain After cardiac surgery (PANDORA) trial is a parallel-group, double-blinded, randomised controlled, single-centre study recruiting 902 participants undergoing MICS. Participants will be randomised in a 1:1 ratio to dexamethasone palmitate (D-PAL) emulsion group and dexamethasone (DSP) group. To investigate the effect of a single bolus perineural administration of D-PAL as an adjuvant treatment to a standard thoracic paravertebral block (TPVB) with ropivacaine decreases the incidence of CPSP in adult patients as compared with single bolus perineural administration of DSP combined with ropivacaine in TPVB. The primary endpoint is the incidence of chronic postoperative pain at 3 months following surgery defined as per the updated International Classification of Diseases. CPSP is defined as a new development of pain or increase in the intensity of pain at the surgical area or projected onto the innervation area of a nerve in this area after a surgical procedure that persists for at least 3 months. The nature and intensity of pain will be evaluated with a Brief Pain Inventory Short Form (BPI-SF) questionnaire.Ethics and dissemination The trial was approved by the Ethics Committee of Xijing Hospital, the First Affiliated Hospital of Air Force Military Medical University (KY20232194-C-1). Results will be submitted for publication in peer-reviewed journals and presented at academic meetings.Trial registration number ClinicalTrials.gov, NCT05920967.